Effect of aspirin intake at bedtime versus on awakening on circadian rhythm of platelet reactivity - Bonten, Tobias N.; Saris, Anno; van Oostrom, Monique J.; Snoep, Jaapjan D.; Rosendaal, Frits R.; Zwaginga, Jaap J.; Eikenboom, Jeroen; van der Meer, Pieter F.; van der Bom, Johanna G. (Thrombosis and Haemostasis, 2014)
The risk of acute cardiovascular events is highest during morning hours, and platelet activity peaks during morning hours. The effect of timing of aspirin intake on circadian rhythm and morning peak of platelet reactivity is not known. It was our objective to evaluate the effect of timing of aspirin intake on circadian rhythm and morning peak of platelet reactivity. A randomised open-label cross-over trial in healthy subjects (n=14) was conducted. Participants used acetylsalicylic acid (80 mg) on awakening or at bedtime for two periods of two weeks, separated by a four-week wash-out period. At the end of both periods blood was drawn every 3 hours to measure COX-1-dependent (VerifyNow- Aspirin; Serum Thromboxane B2 [STxB2]) and COX-1-independent (flow cytometry surface CD62p expression; microaggregation) platelet activity. VerifyNow platelet reactivity over the whole day was similar with intake on awakening and at bedtime (mean difference: –9 [95 % confidence interval (CI) –21 to 4]). However, the morning increase in COX-1-dependent platelet activity was reduced by intake of aspirin at bedtime compared with on awakening (mean difference VerifyNow: –23 Aspirin Reaction Units [CI –50 to 4]; STxB2: –1.7 ng/ml [CI –2.7 to –0.8]). COX-1-independent assays were not affected by aspirin intake or its timing. Low-dose aspirin taken at bedtime compared with intake on awakening reduces COX-1-dependent platelet reactivity during morning hours in healthy subjects. Future clinical trials are required to investigate whether simply switching to aspirin intake at bedtime reduces the risk of cardiovascular events during the high risk morning hours.
Keywords: Aspirin; chronotherapy; circadian rhythm; platelet aggregation; randomised controlled trial